Pengaruh Model Pembelajaran Value Clarification Technique (VCT) Berorientasi Tri Hita Karana Terhadap Sikap Spiritual Dan Sikap Sosial Mahasiswa - L. Heny Nirmayani; I Kadek Edi Yudiana (Edukasi: Jurnal Pendidikan Dasar, 2023)
The purpose of this study was to see the effect of the Tri Hita Karana-oriented Value Clarification Technique (VCT) learning model on the spiritual attitudes and social attitudes. The sample in this study were students of class G and B semester I of the PGSD Department in the 2022/2023 school year. This type of research is quasy experimental research. The data method used in this research is the observation method and the questionnaire method. Observation methods and questionnaires were used to collect data on students' social attitudes and spiritual attitudes. The data analysis used in this study was Manova. Based on the research that has been done, it can be denied that: 1) there is a significant effect of the Tri Hita Karana-oriented VCT learning model with the students' spiritual attitude, 2) there is a significant influence on the Tri Hita-oriented VCT learning model on the student's social attitude, and 3) Simultaneously, there is a significant effect of the Tri Hita Karana oriented VCT learning model on students' spiritual attitudes and social attitudes